Arte, educación y política : Activismos artísticos y saberes emancipadores - Milomes, Ana Magdalena (2017)
This work aims to analyze the art vision —as a tool of social transformation both symbolic and material— expressed by Education Law 26,206 and Resolution 111/10. The aim will be, on the one hand, to investigate the critical power of contemporary artistic languages and the production of discourses capable of modifying the conditions of existence; and, on the other hand, the relation of these artistic-political practices to the curricular frameworks and the ways of transmitting emancipatory knowledge for the construction of diverse, democratic and fair worlds.